Behind the Scenes: How Logistics Shape Space Fantasy Science Fiction Narratives - Paché, Gilles (Technium Social Sciences Journal, 2024)
This research note explores how logistics, though often overlooked, is a central element in space fantasy science fiction narratives. In Frank Herbert’s Dune, the spice—essential for interstellar travel—demonstrates how logistics influences space geopolitics. Star Wars highlights the logistical challenges involved in managing an intergalactic empire, from constructing the Death Stars to coordinating rebel fleets. In Star Trek, space exploration depends on intricate logistics to sustain ships, space stations, and diplomatic relations. Finally, Isaac Asimov’s Foundation illustrates how the collapse of logistics can lead to the downfall of an intergalactic empire. These films and novels reveal that logistics extends beyond mere materials and operations management; it becomes a key question of survival, power, and stability within these fictional universes. Science fiction narratives not only offer insights into future logistics but also prompts reflection on contemporary challenges in supply chain and infrastructure management.